The NLRP3 inflammasome: a therapeutic target of phytochemicals in treating atherosclerosis (a systematic review) - Liu, Yongchao; Wu, Qianyi; Shao, Jing; Mei, Youmin; Zhang, Jie; Xu, Qiuyun; Mao, Liming (Frontiers in Immunology, 2025)
Atherosclerosis (AS) is a chronic inflammatory disease characterized by the gradual accumulation of plaques in arterial walls, with its pathogenesis remaining incompletely understood. Recent studies have highlighted that development of AS is closely associated with the aberrant activation of the NLRP3 inflammasome in the arteries. Inhibition of the NLRP3 inflammasome by natural products and formulae derived from Chinese herbal medicines (CHMs) has been shown to alleviate AS-associated pathologies. However, therapies that effectively and safely target the NLRP3 inflammasome remain limited. This review aims to summarize the key discoveries from recent studies on the effects of these natural products and formulae on the NLRP3 inflammasome in the context of AS treatment. A comprehensive literature search was conducted on databases such as PubMed/MEDLINE up to January 2025, yielding 38 eligible studies. Our analysis indicates that certain therapies can effectively prevent arterial inflammation in animal models by targeting multiple pathways and mechanisms related to the NLRP3 inflammasome. This review summarizes the primary findings of these studies, focusing on the therapeutic effects and underlying mechanisms of action. Based on these insights, we propose future strategies to enhance the efficacy, specificity, and safety of existing natural products and formulae for AS treatment. Additionally, this study offers a perspective for future research that may enhance our understanding of the roles and the mechanisms of CHM-derived phytochemicals and formulae in regulating the NLRP3 inflammasome and treating AS.